Pengaruh Lingkungan Kerja Fisik dan Lingkungan Kerja Nonfisik terhadap Turnover Intention dengan Kepuasan Kerja Sebagai Variabel Intervening Studi Pada PT Citraraya Mandiri Motor - Lilik Muviana (Jurnal Ilmu Manajemen, 2022)
This study examines the relationship between the physical and non-physical work environments on turnover intention through job satisfaction as an intervening variable. The data is collected using convenience sampling. The total respondents obtained are 41 employees from a company by distributing offline questionnaires. This research is a quantitative approach to causality analysis using Structural Equation Modelling (SEM) analysis technique in SmartPLS software version 3.0. This study shows that the physical work environment does not affect employee job satisfaction and turnover intention. The non-physical work environment has a significant positive effect on job satisfaction. The non-physical work environment has a significant negative effect on turnover intention. And Job satisfaction has a significant negative effect on turnover intention. This research implies that the company is conducting training on internalising company values. The company leaders could better provide direction to subordinates at work and offer promotion opportunities for employees with high work performance. To increase job satisfaction and reduce turnover intention, companies can also improve the non-physical work environment by implementing employee policies that do not harm the company and its employees, e.g., continuing to provide WFH employees' salaries.